(NDSTA) Cases reported during the week ended 26 December 1975 - No author listed (Communicable Diseases Intelligence, 1975)
Whole-issue pdf, comprising: Notifiable Diseases in the States and Territories of Australia List A - Communicable diseases notified by medical practitioners, hospitals or diagnostic laboratories. Week ended 26 December 1975 List B - Communicable diseases and agents notified after hospital and laboratory diagnosis. Week ended 26 December 1975 [includes weekly cases notified and accumulative total - year to date]